Primary Delay in Diagnosis in Head and Neck Cancer: Non Covid Causes in Covid-19 Pandemic Era - Thakur, Rishikesh; Thakur, Sanjeev Kumar; Thakur, Sanjeev Kumar (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Corona virus disease (COVID-19) has been one of the cause for delay in diagnosing and management for all non COVID diseases since the pandemic started especially for head neck cancer where exposure of sites are considered high risk for disease spread. Head neck cancer need to be addressed early as per reporting various oncological guidelines in view of better prognosis if addressed early. We evaluated the non- COVID cause for primary delay by patients so that it can be addressed for better oncological care. MATERIAL AND METHODS We evaluated 35 cases of head neck cancer reported in outpatient of department of Otorhinolaryngology and head neck surgery. The inclusion criteria were the subsites( oral cavity, oropharynx, larynx and hypopharynx ) that need to be addressed promptly irrespective of COVID and the patients had given consent. Statistical Package for the Social Sciences (SPSS) version 16 used for statistical analysis and Mann Whitney U test applied for 2 independent variables. RESULTS Patients characteristic, tumor characteristics and symptoms were evaluated. Advanced age (>60 years) and male predominance were seen in 51.4% and 54.3% respectively. Median delay was noticed for 4 months . When variables were evaluated for delay, male sex and village resident showed significant primary delay in comparison to female sex and city residents with p value of 0.003 and 0.03 respectively. CONCLUSION Non COVID cause for primary delay was prevalent. The median delay noticed 4 months and need to be addressed for proper good oncological outcome and proper health care delivery because of when the pandemic will last is not clear.